Factors influencing self-help group members empowerment in Nigeria - Gombe, Sani Yakubu; Suandi, Turiman; Ismail, Ismi Arif; Omar, Zoharah (Mediterranean Center of Social and Educational Research, 2016)
The wide spread of self-help groups (SHGs) in both urban and rural communities in Nigeria and the low empowerment of the members economically, socially, politically and psychologically raises a lot of questions about what exactly is happening, since the primary objective of forming the SHGs is to empower the members holistically. The overall aim of the paper is to identify and discuss the factors influencing SHG member empowerment in Nigerian communities. The paper briefly discusses leadership, cohesiveness, participation, volunteerism, communication, goals/objectives as (Group factors), while age of SHG member, gender, location and marital status as (Personal factors). The paper concludes that understanding why community members remain in their various SHGs or otherwise is very important in empowerment studies and holistic community development. There is every need to keep encouraging community members to form both homogeneous and heterogeneous SHGs to enable elimination of barriers towards participation and allow all community members participate in empowerment process. The paper contributed to the debates on the most influential factors leading to overall empowerment of members in a group setting, it also added to the existing literature on empowerment as an outcome rather than a process only. The paper also recommends that regulatory agencies should be more active in their supervisory and monitoring role in order to identify fake SHGs and those operating below standard and also reward those adhering to ethics and code of conduct; more studies need to be conducted with a view of exploring more factors influencing SHG members empowerment in Nigeria and compare with what is obtained globally to strengthen the system for better performance and management.